The Impact of Financing Structure on Increasing Profitability in Iraqi Islamic Banks: an Analytical Study for the Period (2014–2020) - Karrar Naeem Abdullah; Manal Obaid Fahad (Research Parks Publishers, 2026)
The study seeks to clarify the construct of capital system, its major determinants as well as internal and external finance sources to examine its connection with the profitability in Islamic banking. The study is based on a number of samples which consist of Kurdistan International Islamic Bank for investment and development and the relative Iraqi Bank for Investment and development during the projected period of (2014 -2020). Financial analysis apparatuses were deployed to assess the capital composition through ratios of equity-to-assets, loans and liabilities and deposits-to-liabilities in addition to profitable indicators (ROA, ROE, ROI) which obtained the financial statements. The findings strikingly exhibited that the capital structure is dependent on balancing return risk and a sole reliance on short-term liquidation in comparison with long-term financing which leads to limited profitability as a result of higher cost. Thes study consequently suggests the need for the adoption of effective approach to diversify the capital sources between equity and debt to realize optimum motive that reduces cost and enhances returns. The banks should be careful in implementing their financial projects that have direct impact on return, profitability, liquidity and risk management.